P Penciptaan Produk Perlengkapan Ruang Tunggu Kantor Transformasi Bentuk Jembatan Kolonial Kampung Tinggi Buleleng - I Made Widhya Divabhawana; I Nyoman Suardina; Ni Kadek Karuni (Pusat Penerbitan LP2MPP ISI Denpasar, 2021)
Generally, when someone is waiting there are many opportunities to see and form opinions about the office being visited, so it is necessary to have attractive office waiting room furniture. The purpose of making this work is limited to office waiting room products consisting of: one table, one chair, and wall decoration. The method of creating works is the transformation method, by applying the stages of SP theory. Gustami are the three pillars of art creation including: (1) Exploration, which is the stage of exploring the source of ideas, collecting data, references, processing and analyzing data. (2) The design, built on the acquisition of important points from the formulated analysis, is continued with the visualization of ideas in the form of alternative sketches. The selected sketch is poured into the working drawing, completed with dimensions, (3) Embodiment, making the design so that it has a form. The embodiment process uses several stages, namely: selecting raw materials, breaking wood, shaving wood, making malls, assembling, sanding and finishing. The creation of the work consists of a set of chairs, tables, and wall decorations for the office waiting room. The style of furniture created has a characteristic rustic style, which is a design concept that has a texture that is not smooth or rough and is not finished.